1990
DOI: 10.1007/bf01541930
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of male transsexual typology to psychosocial adjustment

Abstract: In a search to uncover variables predictive of psychosocial adjustment of male transsexuals, this study examined features which have been empirically linked to characteristics of male transsexual typology. Data from 25 male transsexual volunteers were examined by means of multiple regression analysis to determine whether symptoms of introversion, depression, or tension, as well as adjustment to work and gender reorientation could be linked to the typological variables of androphilia, gynephilia, cross-gender f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…As the data in Table 2 indicate, many investigators have observed that earlyonset MtF transsexuals tend to differ from late-onset MtF transsexuals in other clinically important ways. For example, comArch Sex Behav (2010) 39:514-545 533 pared with their late-onset counterparts, early-onset MtF transsexuals usually display more cross-gender behavior during childhood (Docter, 1988;Dolan, 1987;Doorn et al, 1994;Laub & Fisk, 1974;Levine & Lothstein, 1981;Lundström et al,1984;Seil, 1996Seil, , 2004Stoller, 1979Stoller, , 1980; but see Person & Ovesey, 1974a, b) and less cross-gender fetishism (Burns et al, 1990;Docter, 1988;Dolan, 1987;Fisk, 1974a, b;Levine & Lothstein, 1981;Lundström et al, 1984;Person & Ovesey, 1974a, b;Seil, 1996;Stoller, 1979Stoller, , 1980; but see Doorn et al, 1994, andJohnson &Hunt, 1990). In most reports, late-onset MtF transsexuals have been described as greatly outnumbering their early-onset counterparts (Dolan, 1987;Levine & Lothstein, 1981;Lundström et al, 1984;Seil, 2004;Stoller, 1980; but see Doorn et al, 1994, andJohansson et al, 2009).…”
Section: Typologies Based On Age Of Onsetmentioning
confidence: 96%
See 2 more Smart Citations
“…As the data in Table 2 indicate, many investigators have observed that earlyonset MtF transsexuals tend to differ from late-onset MtF transsexuals in other clinically important ways. For example, comArch Sex Behav (2010) 39:514-545 533 pared with their late-onset counterparts, early-onset MtF transsexuals usually display more cross-gender behavior during childhood (Docter, 1988;Dolan, 1987;Doorn et al, 1994;Laub & Fisk, 1974;Levine & Lothstein, 1981;Lundström et al,1984;Seil, 1996Seil, , 2004Stoller, 1979Stoller, , 1980; but see Person & Ovesey, 1974a, b) and less cross-gender fetishism (Burns et al, 1990;Docter, 1988;Dolan, 1987;Fisk, 1974a, b;Levine & Lothstein, 1981;Lundström et al, 1984;Person & Ovesey, 1974a, b;Seil, 1996;Stoller, 1979Stoller, , 1980; but see Doorn et al, 1994, andJohnson &Hunt, 1990). In most reports, late-onset MtF transsexuals have been described as greatly outnumbering their early-onset counterparts (Dolan, 1987;Levine & Lothstein, 1981;Lundström et al, 1984;Seil, 2004;Stoller, 1980; but see Doorn et al, 1994, andJohansson et al, 2009).…”
Section: Typologies Based On Age Of Onsetmentioning
confidence: 96%
“…Two important studies, conducted by Freund et al (1982) and Johnson and Hunt (1990), addressed the comparative descriptive value of a number of features associated with MtF transsexualism; both studies found sexual orientation, and gynephilia specifically, to be an important, and arguably the most important, descriptive feature. As previously discussed, Freund et al studied 136 male patients with varying degrees of cross-gender identity, most of whom were transsexuals or ''borderline transsexuals.''…”
Section: Typologies Based On Sexual Orientationmentioning
confidence: 98%
See 1 more Smart Citation
“…Among transsexuals, Johnson and Hunt (1990) found gynephilia was significantly positively correlated with sexual arousal to cross-gender fantasy, and significantly negatively correlated with feminine gender identity in childhood. More recent studies have also reported the existence of cross-gender sexual arousal among transsexuals (Docter & Fleming, 2001;Lawrence, 2003;Walworth, 1997).…”
Section: Introductionmentioning
confidence: 92%
“…Langevin (1985) concluded that "gender identity may be as significant a component in transvestism as erotic needs" (p. 214). Johnson and Hunt (1990) hypothesized that autogynephilic transsexuals experience real gender identity conflicts, just as androphilic transsexuals do, but resolve these conflicts later in life. Levine (1993) argued that autogynephilic eroticism could be an effect rather than a cause of atypical gender identity and proposed that "cross-dressing and ... autogynephilic fantasy are the external and internal manifestations of the same phenomenon-the conscious experience of the self as at least partially female" (p. 135).…”
Section: Autogynephilia Gender Identity and The Transsexual Motivementioning
confidence: 99%